Civil construction waste management: bibliometric analysis between 2010 and 2020 (Research, Society and Development, 2021)
The civil construction contributes to environmental degradation due to the impacts caused to the environment and to the volume of waste disposed of without adequate treatment. This scenario influences researchers through studies linked to the thematic of Civil Construction Waste Management (CCWM) to find ways to reduce these impacts. Based on this, this study sought to identify research trends on the CCWM thematic and to present an analysis of the evolution of publications, through the mapping of countries, authors and co-occurrence of keywords. The methodology used was the bibliometric study based on scientific productions from the Scopus database, considering the period between 2010 and 2020. The aspects analyzed were year of publication, publications by countries, publications by journals, and the relations of citation, authorship and co-occurrence of the keywords through the analysis of network maps. The results pointed that there is an growth trend in the number of articles published from 2016, with China being the country with the highest volume of publications, and featuring reference authors, also contributing with a comprehensive view of future research paths on CCWM thematic.